Oxidant and antioxidant status of tissues of freshwater crayfish (Astacus leptodactylus esch., 1823) from different stations in the keban dam lake - Barim, Ozden; Benzer, Fulya; Erisir, Mine; Dorucu, Mustafa (My University, 2009)
The aim of this study was to investigate the antioxidant (reduced glutathione (GSH), glutathione peroxidase (GSH-Px)) and the oxidant (nitric oxide (NO), lipid peroxidation (MDA)) status of hepatopancreas, gills and muscle tissues of freshwater crayfish (A. leptodactylus) collected from the Keban Dam Lake and to evaluate the effect of aquatic pollution on these parameters. The crayfish samples were obtained from contaminated (Agin) and uncontaminated (Aydincik) stations at Keban Dam Lake in August 2007. The GSH-Px activity was significantly lower (p<0.05) in the gills and significantly higher (p<001) in muscle tissues samples from crayfish collected at the contaminated station compared to those collected from the uncontaminated station. GSH levels were lower in the gill and muscle of the crayfish collected at the contaminated station (p<0.05, p<0.001 respectively). No significant different in the levels of the GSH-Px and GSH in the hepatopancreas was observed between stations. The MDA levels were significantly higher in hepatopancreas, gill and muscle of the crayfish in the contaminated station (p<0.05, p<0.05, p<0.01). However, NO level was found significantly higher in the hepatopancreas of crayfish from the contaminated station (p<0.01), whereas there was no difference between stations in gill or muscle tissue NO. The noted tissue distributions of the investigated parameters most likely reflected different metabolic activities and different responses to environmental conditions in the examined tissues. In particular, MDA can be a sensitive indicator of aquatic pollution.
Keywords: Astacus leptodactylus; Keban dam lake; Oxidant and antioxidant status; Pollution